Polyphenols characterization and toxicological evaluation of pterospartum tridentatum leaf water extracts - Ferreira, Fernanda M. (2013)
Pterospartum tridentatum Willk. (prickled broom) is an autochthonous and common plant in Portugal. Leaves and stems are normally used in cooking, to flavour rice, roast meat or hunting animals. Leaves are also used as a condiment in fresh salads and, despite of its traditional use, no toxicological evaluation has been performed. P. tridentatum leaves aqueous extract ESI-MS spectrum revealed the presence of several luteolin and isorhamnetin derived phenolic compounds, which can be associated to the health benefits claimed for this plant species. Still, P. tridentatum leaves extract (up to 100 µg plant extract.mg-1 protein) stimulated state 4 and FCCP-stimulated liver mitochondria respiratory rates and inhibited the state 3 respiratory rate. Respiratory control ratio was diminished, indicating a decrease in phosphorylative efficiency due to inner mitochondrial membrane induced by P. tridentatum leaves extract. Nevertheless, previous results, cytotoxicity evaluation by MTT assay (50 and 125 µg plant extract) showed no significant decrease on HepG2 cell viability. Overall, the present study suggests that the consumption of P. tridentatum leaves should be regarded as safe.